2018
DOI: 10.24198/pjd.vol25no1.15427
|View full text |Cite
|
Sign up to set email alerts
|

Teeth re-whitening effect of strawberry juice on coffee stained teeth

Abstract: Many people favor coffee. However, regarding health and aesthetic dentistry, coffee gives a negative effect. Tanin in coffee causes a brown stain on the tooth surface. Therefore, in aesthetic dental care, teeth whitening has become popular matter. One of the natural ingredients used for teeth whitening treatment is strawberry. The purpose of this study was to obtained data regarding the effect of strawberry juice on the re-whitening process of the coffee-stained tooth enamel surface. This study was a pure expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The results of the study were consistent with the research conducted by Pramesti et al showed that strawberry consumption can remove stains caused by soda, wine and coffee. The natural tooth whitening can happen when consumed in proper time and concentration [35].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study were consistent with the research conducted by Pramesti et al showed that strawberry consumption can remove stains caused by soda, wine and coffee. The natural tooth whitening can happen when consumed in proper time and concentration [35].…”
Section: Discussionmentioning
confidence: 99%
“…Selain apel, buah stroberi diketahui memiliki kandungan ellagic acid dan hidrogen peroksida yang dapat menyebabkan warna email menjadi lebih terang. 5,7 Buah semangka (Citrulluls lanatus) memiliki kandungan asam malat yang lebih besar yaitu 99%, dibanding buah apel 95%. Buah semangka juga mempunyai kandungan hidrogen peroksida seperti stroberi.…”
Section: Pendahuluanunclassified
“…7 In dentistry, lime fruit (Citrus aurantifolia) is used to whiten teeth, clean nicotine plaque, and reduce plaque score. [7][8][9][10][11] It has antibacterial properties due to essential oil content consisting of active agent : flavonoid, polyphenol, and saponin. 12 These compounds can denature bacterial proteins thereby inhibiting bacterial growth.…”
Section: Introductionmentioning
confidence: 99%